Pediatric palliative medicine in Brazil: an ethical reflection of medical practice - de Almeida Rocha, Anderson; Freitas, Lurdiano; Cesconetto, Juliana; Rebouças, Lara Calhau; Salomão, Vitória Barreto; Nunes, Rui Manuel Lopes (Acta Bioethica, 2023)
The ethical barriers involved in the practice of pediatric palliative medicine remain high and challenging. In termsof medical ethics, attention should be paid to culture, religion and family values, in order to promote adequate care forcaregivers, even in case of loss of a patient, promoting a bereavement process with less suffering. The data were qualitativelyanalyzed by IRAMUTEQ software, with a high degree of significance of essay responses on ethics related to palliative care inpediatrics. Discussions about prognosis, goals of care, and treatment options can be very difficult, as legally supported palliativecare alternatives may diverge from the wishes of the family. We conclude that divergences exist between the application ofpalliative medicine and ethics regarding acceptance and end-of-life management of pediatric patients. Ethical challenges areconstantly complex situations in which palliative physicians must relate legal concepts, knowledge and family values, whichoften conflict. The quality of palliative care depends initially on the ability of specialized professionals to identify and explainthe ethical issues that generate conflict or uncertainty, in addition to raising discussions with the family about the medical,moral and legal issues surrounding the difficult situation.